A Study Of 7th Grade Sudent's Views on Student-Teacher Relationship and its Effect on Academic Grades at School Level in Quetta District - Seema Azeem (lppm Universitas Negeri Jakarta, 2019)
The study explores the views of students, and investigates the effect of their views on their academic performances in the form of grades. The hypothesis tested in this study was thatthe positive relationshipbetween teacher and students leads to a high academic achievement. This research was conducted in Elementary schools of Quetta. The sample used for this study was 6 Elementary schools, both of male and female and the sample consisted of 200 students. The students were selected randomly from the chosen 6 schools. The nature of the study was quantitative and questionnaire was used for the collection of data. The outcomes of the study  reveal that a correlation exists between student relations with their teachers and the findings of the regression test show that positive relationship of teachers with their student impact student achievement.